2022
DOI: 10.1021/acsomega.1c06572
|View full text |Cite
|
Sign up to set email alerts
|

Electrothermal Performance of Heaters Based on Laser-Induced Graphene on Aramid Fabric

Abstract: Nanostructured heaters based on laser-induced graphene (LIG) are promising for heat generation and temperature control in a variety of applications due to their high efficiency as well as a fast, facile, and highly scalable fabrication process. While recent studies have shown that LIG can be written on a wide range of precursors, the reports on LIG-based heaters are mainly limited to polyimide film substrates. Here, we develop and characterize nanostructured heaters by direct writing of laser-induced graphene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…is the heat conduction distance. The thickness of the substrate is the key (b) laser-induced method [22], and (c) ultrafast laser ablation method [23]. Reprinted with permission from MDPI, ACS, and ELSEVIER.…”
Section: Heat Transfer Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…is the heat conduction distance. The thickness of the substrate is the key (b) laser-induced method [22], and (c) ultrafast laser ablation method [23]. Reprinted with permission from MDPI, ACS, and ELSEVIER.…”
Section: Heat Transfer Modelsmentioning
confidence: 99%
“… Structures of microheaters based on graphene fabricated with ( a ) inkjet-printed method [ 21 ], ( b ) laser-induced method [ 22 ], and ( c ) ultrafast laser ablation method [ 23 ]. Reprinted with permission from MDPI, ACS, and ELSEVIER.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, owing to graphene's advantages such as flexibility, high‐electron conductivity, transparency, and mechanical robustness, it has been extensively used in variety of new functional materials especially for the applications such as defrosters and defoggers, anti‐icing, vehicle windows, photothermal materials, interfacial heating devices and so on 27 . Some of the recent reports on graphene based joule heaters explain the heating efficiency of the graphene‐polymer system considering the highest temperature reached under specific voltage and input electrical energy 28,29 . It has been suggested that decreasing the resistance of graphene‐polymer composites/films is the key factor in enhancing the joule heating efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…27 Some of the recent reports on graphene based joule heaters explain the heating efficiency of the graphene-polymer system considering the highest temperature reached under specific voltage and input electrical energy. 28,29 It has been suggested that decreasing the resistance of graphene-polymer composites/films is the key factor in enhancing the joule heating efficiency. PVDF due to its properties such as ease of solubility, film forming ability, chemical resistance and thermal stability up to 170 C, it is one of the best polymer matrices to host the graphene sheets through dipole-dipole interactions for the fabrication of flexible self-heating films or composites.…”
Section: Introductionmentioning
confidence: 99%